2001
DOI: 10.1136/ard.60.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of histological and immunohistological abnormalities in sublabial salivary gland biopsy specimens following treatment with corticosteroids in Sjogren's syndrome

Abstract: Sjögren's syndrome (SS) is a chronic autoimmune disease characterised by specific lesions in exocrine glands, so sublabial minor salivary gland biopsy (SLGB) plays an important part in its diagnosis. The extent and composition of the lymphocytic infiltrate in SLGB specimens can be considered as target organ specific parameters. They are quantified after histological and immunohistological examination by a focus score (describing the extent of the infiltrate) and IgA% score (describing the composition of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 10 publications
0
29
0
2
Order By: Relevance
“…Other rheumatic diseases, exogenic factors such as nicotine abuse, aging effects, and chronic nonspecific sialadenitis frequently exhibit lymphocytic focus scores ≥1. Moreover, the Chisholm and Mason scoring system does not include a score for burnout of salivary glands [43][44][45][46][47]. Bodeutsch established quantitative immunohistochemical assessment of IgA-positive plasma cells in minor salivary gland samples, resulting in improved sensitivity and specificity of 96 % and 99 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other rheumatic diseases, exogenic factors such as nicotine abuse, aging effects, and chronic nonspecific sialadenitis frequently exhibit lymphocytic focus scores ≥1. Moreover, the Chisholm and Mason scoring system does not include a score for burnout of salivary glands [43][44][45][46][47]. Bodeutsch established quantitative immunohistochemical assessment of IgA-positive plasma cells in minor salivary gland samples, resulting in improved sensitivity and specificity of 96 % and 99 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, corticosteroids were concomitantly administered in 13 of 28 subjects (46%) with secondary Sjögren's syndrome, versus only 8 of 72 subjects (11%) with primary Sjögren's syndrome. Corticosteroids have been reported to have an improving effect on Sjögren's syndrome [19,20]. Further evidence suggesting that these concomitantly administered drugs may have influenced the results of the study was that in the placebo group, while almost no increase in salivary secretion was seen in subjects with primary Sjögren's syndrome, a marked salivary secretion increasing effect was observed in subjects with secondary Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 77%
“…Zandbelt et al described patients with SS treated with high doses of corticosteroids, who demonstrated an improvement in the main clinical, histological, and immunohistological features after treatment (6) .Sonia et alreported agood response with MMF in SS patients (7) In addition toDean et al who reported agood response with this agent in TIN (8) .…”
Section: Discussionmentioning
confidence: 98%